REDESCRIPCIÓN DE CENTRIS RODOPHTHALMA PÉREZ 1911 (HYMENOPTERA: ANTHOPHORIDAE) Y CLAVE PARA LAS ESPECIES DEL GÉNERO DE LA IIIY IV REGIONES DE CHILE - Chiappa, Elizabeth (Acta Entomológica Chilena, 2022)
A redescription of Centris rodophthalma Pérez 1911, intented to give a better picture of this species, is made. A key is given for the species of Centris that occur simpatrically to C. rodophthalma.